Bee louse, bee fly, braulid, Braula coeca Nitzsch (Insecta: Diptera: Braulidae) - James D. Ellis; C.M. Zettel Nalen (EDIS, 2010)
EENY472, a 3-page illustrated fact sheet by James D. Ellis and C.M. Zettel Nalen, is part of the Featured Creatures collection. It describes this wingless fly that lives as a commensalist in western honeybee colonies — distribution, description, life cycle and behavior and management. Includes references. Published by the UF Department of Entomology and Nematology, April 2010.